2003
DOI: 10.1128/mcb.23.14.4870-4881.2003
|View full text |Cite
|
Sign up to set email alerts
|

S100B Inhibits Myogenic Differentiation and Myotube Formation in a RAGE-Independent Manner

Abstract: S100B is a Ca2؉ -modulated protein of the EF-hand type with both intracellular and extracellular roles. S100B, which is most abundant in the brain, has been shown to exert trophic and toxic effects on neurons depending on the concentration attained in the extracellular space. S100B is also found in normal serum, and its serum concentration increases in several nervous and nonnervous pathological conditions, suggesting that S100B-expressing cells outside the brain might release the protein and S100B might exert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
109
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 51 publications
10
109
0
1
Order By: Relevance
“…While in other cell types responsive to S100B such as neurons and microglia the receptor for advanced glycation end products (RAGE) was demonstrated to bind S100B and to transduce the regulatory effects of S100B (20,23) and while myoblasts were observed to express RAGE (mRNA and protein) constitutively (51), no such role for RAGE could be documented in the case of the inhibitory effects of S100B on myoblasts. In fact, S100B inhibited myoblast differentiation and myotube formation in L6 myoblasts stably overexpressing either full-length RAGE (L6/RAGE myoblasts) or a RAGE mutant lacking the cytoplasmic and transducing domain (L6/ RAGE⌬cyto myoblasts) (51). Collectively, these data suggested that S100B negatively regulated myogenesis in vitro by binding to a receptor other than RAGE.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…While in other cell types responsive to S100B such as neurons and microglia the receptor for advanced glycation end products (RAGE) was demonstrated to bind S100B and to transduce the regulatory effects of S100B (20,23) and while myoblasts were observed to express RAGE (mRNA and protein) constitutively (51), no such role for RAGE could be documented in the case of the inhibitory effects of S100B on myoblasts. In fact, S100B inhibited myoblast differentiation and myotube formation in L6 myoblasts stably overexpressing either full-length RAGE (L6/RAGE myoblasts) or a RAGE mutant lacking the cytoplasmic and transducing domain (L6/ RAGE⌬cyto myoblasts) (51). Collectively, these data suggested that S100B negatively regulated myogenesis in vitro by binding to a receptor other than RAGE.…”
mentioning
confidence: 93%
“…Total cytoplasmic RNA was isolated from L6 myoblasts by the Trizol reagent method. Subsequent steps were done as described previously (51). After amplification, samples (10 l) of each PCR mixture were electrophoresed on a 1.2% agarose gel and reverse transcription-PCR (RT-PCR) products were revealed by ethidium bromide staining.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations